KORELASI ANTARA HASIL BELAJAR KITAB SAFINATUN NAJAH DENGAN PELAKSANAAN IBADAH MAHDHAH SHALAT SANTRI KELAS II MADRASAH DINIYAH HIDAYATUL MUBTADI’IN DESA GOWONG KECAMATAN BRUNO KABUPATEN PURWOREJO - Naimah Mudlofir; Prawidya Lestari (Al Ghazali, 2020)
Faith and piety do not go away from prayer education which is a great benefit to life. Prayers can prevent profanity and rebellion, prayer improves discipline in daily life, prayers open the heart to truth and many more benefits of prayer in the spirit. Thus prayer becomes a fundamental measure for measuring the quality of one's faith. So prayers need to be learned, known properly and practiced regularly. For the benefit to be truly felt in everyday life. This type of research is field research with a quantitative approach. Data collection techniques using values and questionnaires. Data analysis techniques using Pearson Product Moment correlation formula. The learning outcomes of the Safinatun Najah class II santri in the Diniyah Hidayatul Mubtadi'in Madrasah, Gowong Village, Bruno District, Purworejo Regency, are included in the "quite good" category. This can be seen from the mean learning outcomes of the Safinatun Najah Book (variable X) which is 82 are at intervals of 81-85. The implementation of Mahdhah Shalat for students of class II at Diniyah Hidayatul Mubtadi'in Madrasah, Gowong Village, Bruno District, Purworejo Regency, is included in the "good enough" category. intervals of 70-74. Based on quantitative analysis, there is a positive and significant correlation between the learning outcomes of the Book of Safinatun Najah and the implementation of the Mahdhah Shalat santri. Evident from the results of the empirical correlation coefficient (r count) = 0.789 greater than the Pearson Product Moment coefficient (r table) at a significance level of 5% = 0.482 and r table at a significant level of 1% = 0.606. Thus the hypothesis that the researcher proposes can be accepted that "there is a positive or significant correlation or correlation between the results of the study of the Book of Safinatun Najah with the implementation of the Mahdhah prayer for students of class II Madrasah Diniyah Hidayatul Mubtadi'in, Gowong Village, Bruno District, Purworejo District".